Biomechanical comparison of plate and screw fixation in anterior pelvic ring fractures with low bone mineral density. Issue 7 (July 2016) - Acklin, Yves P.; Zderic, Ivan; Buschbaum, Jan; Varga, Peter; Inzana, Jason A.; Grechenig, Stephan; Richards, R. Geoff; Gueorguiev, Boyko; Schmitz, Paul
Abstract: Introduction: Osteosynthesis of anterior pubic ramus fractures can be challenging, especially in poor bone quality. The aim of the present study was to compare plate and retrograde endomedullary screw fixation of the superior pubic ramus with low bone mineral density (BMD). Materials and methods: Twelve human cadaveric hemi-pelvises were analyzed in a matched pair study design. BMD of the specimens was 35 ± 30 mgHA/cm 3, as measured in the fifth lumbar vertebra. A simulated two-fragment superior pubic ramus fracture model was fixed with either a 7.3-mm cannulated retrograde screw (Group 1) or a 10-hole 3.5-mm reconstruction plate (Group 2). Cyclic progressively increasing axial loading was applied through the acetabulum. Relative interfragmentary movements were captured using an optical motion tracking system. Results: Initial axial construct stiffness was 424 ± 116.1 N/mm in Group 1 and 464 ± 69.7 N/mm in Group 2, with no significant difference ( p  = 0.345). Displacement and gap angle at the fracture site during cyclic loading were significantly higher in Group 1 compared to Group 2. Cycles to failure, based on clinically relevant criteria, were significantly lower in Group 1 (3469 ± 1837) compared to Group 2 (10, 226 ± 3295) ( p  = 0.028). Failure mode in Group 1 was characterized by screw cutting through the cancellous bone. In Group 2 the specimens exclusively failed by plate bending. Conclusions: From biomechanical point of view, pubic ramus stabilization with plate osteosynthesis is superior compared to a single retrograde screw fixation in osteoporotic bone. However, the extensive surgical approach needed for plating must be considered.